2016
DOI: 10.1088/0957-4484/27/26/265602
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-controlled self-assembly of amorphous-crystalline nanogratings in silicon

Abstract: Self-assembly (SA) of molecular units to form regular, periodic extended structures is a powerful bottom-up technique for nanopatterning, inspired by nature. SA can be triggered in all classes of solid materials, for instance, by femtosecond laser pulses leading to the formation of laser-induced periodic surface structures (LIPSS) with a period slightly shorter than the laser wavelength. This approach, though, typically involves considerable material ablation, which leads to an unwanted increase of the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 33 publications
2
48
1
1
Order By: Relevance
“…1(b)). A similar behavior of amorphous fringe formation and transition to ablation has been reported upon irradiation with 370 fs, 1030 nm laser pulses, although in that case it was at lower N-values, leading to a better fringe homogeneity and alignment 16 . The non-circular shape of the ablation region is a consequence of the directional surface wave triggered at the fringe structures, which is more efficient along the direction of the laser polarization vector, leading to a horizontal enlargement of the ablated region 20 .…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…1(b)). A similar behavior of amorphous fringe formation and transition to ablation has been reported upon irradiation with 370 fs, 1030 nm laser pulses, although in that case it was at lower N-values, leading to a better fringe homogeneity and alignment 16 . The non-circular shape of the ablation region is a consequence of the directional surface wave triggered at the fringe structures, which is more efficient along the direction of the laser polarization vector, leading to a horizontal enlargement of the ablated region 20 .…”
Section: Resultssupporting
confidence: 73%
“…A powerful method to improve fringe homogeneity and alignment, as well as to extend fringes in 2D, is to scan the laser spot over the surface at a well-defined repetition rate and speed 16 . Figure 2(a) shows the best result for a structure written in Si while moving the sample, under similar conditions as those used in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using nanosecond laser irradiation, Pena et al produced micrometer-sized amorphous humps with a height of a few nanometers 18 . Recently, it has been shown that Laser-Induced Periodic Surface Structures (LIPSS) in form of alternating amorphous and crystalline fringes can be fabricated by scanning the laser beam over the sample surface, employing an adequate choice of spot size, repetition rate and scan velocity 19,20 . In the present work we present a simple strategy to fabricate surface-depressed annular amorphous rings with a central crystalline disk, temporally resolve their formation process, and show how these structures can be scaled and stitched together to form arrays with different symmetries.…”
mentioning
confidence: 99%